Predictors to Mental Well-Being at Workplace: A Quantitative Case Study Among Administrative Staff of a Public University in Malaysia - Ahmad Dani, Mar’Ain; Saad, Nurulwahida; Samsuddin, Niza; Ibrahim, Muhamad Ariff; Md Nizar, Khairunnisa; Mohd Amir, Muhammad Afiq Danial; Wan Abdullah, Wan Najihah Nurashikin; Mohd Nazori, Mohd Nazir (IIUM Medical Journal Malaysia, 2025)
INTRODUCTION: The Malaysian Public Service Department reported many staff were at risk of mental health crisis or illness and an independent study revealed concerning rate of suicidal ideation. This study intends to: (a) describe the level of mental health literacy (MHL), mental health self-efficacy (MHSE), and mental well-being (MWB) among university administrative staffs, and (b) explore the dynamic influence between mental health literacy, mental health self-efficacy, and mental well-being. MATERIALS AND METHODS: A cross-sectional study using validated questionnaires was done on 91 administrative staff in one public university in Malaysia. The questionnaire consists of 37 items measuring MHL (subdimensions: knowledge, erroneous belief, first aid, and self-help), MHSE (subdimensions: optimism, factor coping, and advocacy), and MWB. Data was analysed using descriptive statistics, Pearson’s correlation, and multiple linear regression. RESULTS: The mean scores for subdimensions of MHSE ranged from 14.2 to 28.6 (SD=2.73 to 4.45), subdimension of MHL from 6.1 to 25.5 (SD=2.17 to 3.35), and MWB was 18.5 (SD=3.36). Correlation analyses revealed all subdimensions of MHSE and MHL, as well as MWB showed significant weak to strong correlation (r=0.22 to 0.69). Only optimism subdimension of MHSE retained significance in predicting MWB (B=0.43) and among MHL subdimensions, only first aid retained significant prediction to optimism. CONCLUSION: The findings provide valuable insights to the dynamic role between subdimensions of MHL and MHSE, as well as their contribution towards MWB. Healthcare professionals should consider this dynamic into designing mental health promotion activity.